Application and comparison of five risk assessment methods in ferrous metal foundry enterprises with silica dust concentration exceeding the limit posts - Qimeng Li; Xiaoying Li; Ge Qin; Yuanmeng Qi; Jie Liu; Xiaocui Tang; Di Wu; Changfu Hao; Sihua Wang (Frontiers in Public Health)
BackgroundExplore methods to accurately reflect the risk level of ferrous metal foundry workplaces when the silica dust concentration exceeds the limit, and provide a basis for the application of risk assessment techniques in key industries with occupational exposure to silica dust.MethodsThe survey was conducted in 25 ferrous metal casting industries in Henan Province, China. Five occupational health risk assessment (OHRA) methods, including Risk index method, Hazard grading method, International Council on Mining and Metals model, The synthesis index method, and The exposure ratio method, were used to assess the occupational health risk of the workplaces that produced silica dust and the concentration of silica dust exceeded the occupational exposure limits (OELs), and to compare the results of the different methods.ResultsThe risk index assessment method yielded one job of mild hazard, seven job of moderate hazard, fifteen jobs of high hazard, and forty-four jobs of extreme hazard. The hazard classification method resulted in two jobs of mild hazard, six jobs of moderate hazard, and fifty-nine jobs of high hazard. The ICMM qualitative method identified fifteen jobs of moderate risk and fifty-two jobs of high risk. The synthesis index method revealed nine jobs of moderate risk and fifty-eight jobs of high risk. The exposure ratio method identified ten jobs of high risk and fifty-seven jobs of extremely high risk. The results obtained from the synthesis index method showed relatively lower levels, except for the index method, there was a certain correlation (r: 0.541–0.798, P < 0.05) and consistency (kapa: 0.521–0.561, P < 0.05) with the remaining four methods.ConclusionThis study shows that although there are some differences in the results of different OHRA methods, there is also some correlation between them, which can corroborate each other and enhance the reliability of the assessment results. In practical application, appropriate assessment methods should be selected according to specific situations and the results of multiple methods should be combined and analyzed comprehensively to ensure accurate identification and assessment of occupational hazards and provide a scientific basis for improving occupational safety and health management.